Dans les méandres de la littérature dystopique : le pouvoir de l’art contre l’art du pouvoir - Ayed, Kawthar (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In this paper, the author examines the distortion of the past and the perversion ofart in works of speculative dystopian fiction. Without history, there is no longer a past ora future; only the present persists as a perpetual replication of the same structures. In 1984,everything is constantly rewritten in minute detail. In Globalia, the system wages a fierce waragainst history. Art is either recuperated or condemned to burn at the stake of state power(Fahrenheit 451). However, discovering art objects from past times and reading literary workssignal a change of course which raises conscience and even leads to acts of resistance. Indystopian speculative literature, resistance acquires a symbolic dimension: Despite reigningdarkness, there seems to appear a gleam of hope thanks to art and to literature.